في إثراء وترويج الإعلان السياحي (Motion Graphic) التصميم الجر افيكي ودور الرسوم التوضيحية المتحركة. - بهاء مصطفى; عبير إبراهيم (Dirasat: Human & Social Sciences, 2023)
This article focuses on the role of graphic design and animated illustrations in enhancing and promoting tourism advertising in the Arab world. The study aims to identify the challenges facing the design of animations in this context and to provide positive solutions for improving these designs. The study employs a descriptive analytical methodology and highlights the importance of using digital technology in tourism promotion, as animations contribute to attracting tourists' attention and enhancing the tourism experience. It also emphasizes the necessity for designers to be familiar with all modern design software to ensure the quality of their work.